2019
DOI: 10.24090/jk.v7i2.3558
|View full text |Cite
|
Sign up to set email alerts
|

Keefektifan Model Eliciting Activities Ditinjau Dari Kemampuan Berpikir Kritis dan Pemahaman Konsep Pada Pembelajaran IPA

Abstract: Pembelajaran IPA pada  kurikulum 2013 yang diterapkan pada SMP Empu Tantular perlu untuk diamati karena di SMP Empu Tantular pembelajaran IPA masih berorientasi pada guru dan belum sesuai dengan perubahan pada kurikulum 2013. Hal ini mengakibatkan peserta didik cenderung hanya menerima yang dijelaskan guru tanpa mengetahui makna pembelajaran tersebut. Aktivitas peserta didikpun dalam kelas cenderung menghafal dan mendengarkan apa yang diterangkan guru. Hal tersebut berpengaruh pada rendahnya kemampuan berpikir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The application of active-based social learning, practicalapproaches to problem solving, and project-based learning have been witnessed as a way of improving the students' perception of learning, enhancing positive selfesteem, and moving the rate of educational progress according to Abaniel (2021). Besides, research proved that the students mastered the concepts more effectively, academic achievements increased, and students developed meta cognitive skills (Kurniawan, 2019). In addition to that, research on using the approach of modeled elicitation activities has been found to enhance the learner's critical thinking ability, understanding of concepts, and learning activities (Ogunji et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of active-based social learning, practicalapproaches to problem solving, and project-based learning have been witnessed as a way of improving the students' perception of learning, enhancing positive selfesteem, and moving the rate of educational progress according to Abaniel (2021). Besides, research proved that the students mastered the concepts more effectively, academic achievements increased, and students developed meta cognitive skills (Kurniawan, 2019). In addition to that, research on using the approach of modeled elicitation activities has been found to enhance the learner's critical thinking ability, understanding of concepts, and learning activities (Ogunji et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ditemukan bahwa metode Socrates efektif dalam memunculkan tanggapan bijaksana dari kelas. Nurwantoro (2015) menyelidiki dampak pengajaran Socrates terhadap kemampuan berpikir kritis siswa. Temuan studinya memperkuat penelitian sebelumnya yang menunjukkan efek positif dari instruksi Socrates pada keterampilan berpikir kritis siswa melalui penggunaan pengujian hipotesis untuk menentukan apakah pendekatan Socrates benar-benar meningkatkan kemampuan berpikir kritis siswa atau tidak.…”
Section: Hasilunclassified